Tropes, universals and the philosophy of mind : essays at the boundary of ontology and philosophical psychology - Gozzano, Simone; Orilia, Francesco, 1956- (Philosophische Analyse, 2008)
The ontological debate on the nature of properties is alive as ever. Mainly, they are viewed either as universals or tropes (abstract particulars), an alternative with an immediate impact on what events are taken to be. Although much inquiry in philosophy of mind is done without a full awareness of it, some recent works suggest that the choice may have far-reaching consequences on central topics of this discipline, e.g., token physicalism, multiple realizability, mental causation, perception, introspection, self-awareness. This book explores the extent to which this is true with novel contribu.